HYGIENIC REQUIREMENTS FOR CHILDREN’S TOYS AND CLOTHES - Tuxtaeva M.M (Ta’lim innovatsiyasi va integratsiyasi, 2023)
Abstract: Sanitary control of toys is carried out in several stages. The quality of raw materials used in the production of toys, adherence to technical conditions during production, when various changes are made to new materials and technological processes, when it comes to children's institutions in order to carry out current sanitary control over the place and conditions of sale of toys.